DAMPAK PERUBAHAN SISTEM NILAI TERHADAP TARI BEDHAYA SURYA SUMIRAT SEBAGAI KREATIVITAS TARI BEDHAYA BARU DI MANGKUNEGARAN - Suharji, - (Harmonia: Journal of Arts Research and Education, 2009)
Changes in society have an impact on culture and creativity. Changes in societywill lead to changes in orientation to the values espoused. Among previousMangkunegaran temple, not allowed to create a dish Bedhaya dance, becausedance Bedhaya considered sacred dance, which should only be presented in theenvironment Kasunanan Sultanate of Surakarta and Yogyakarta. Because ofchanges in value systems and supporting artists, then in Mangkunegaran thencreated Bedhaya dance. Bedhaya dance originally created the dance BedhayaAnglir clouds as a monument honors the first Mangkunegara services. In theprocess, because internal and external influences, the creation of dance BedhayaSumirat Surya Bedhaya dance that resembles the other. Surya Bedhaya DanceDance Sumirat is a new creation as the creativity to meet the need forentertainment. Surya Sumirat Bedhaya Dance is a fusion of traditional dance andcontemporary dance. Location of novelty, observed through the makeup,dressing, dance movement and impression of movement. Surya SumiratBedhaya Dance performed according to the needs. Dance Bedhaya hasundergone many changes in function and mobility, although his soul was stillreflects the nature of female soldiers.Kata Kunci: Surya Sumirat, Bedhaya Baru, Mangkunegaran